The laforguian landscape: towards a cognitive reading of spatialised neurotic thinking - Leparoux, Clemente (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The main aims of this paper are to highlight the functions of one of the main leitmotivs of Laforgue's poetry: the landscape. Both visual and musical, the poetic landscape will be analysed thanks to the novel tools of the cognitive sciences. It is convenient to evidence that it expresses a range of perceptions and emotions that give rise to ryhtmic constructions and murky symbols. The landscape externalizes and metaphorises, in its structure, the functionning and consequences of the neurotic disorder in the subject's perception of his environment and of himself in space, considering emotion and homeostasis, as if it was a second skin that would somatise any erroneous movement of thinking.
Keywords: Laforgue; Poetry; Cognition; Landscape; Homeostasis; Interoception; Somatization; Kinesthesia; Neurosis; Decadentism